An Experimental Study of Customer Effort, Expectation, and Satisfaction - Cardozo, Richard N. (Journal of Marketing Research, 1965)
Results of a laboratory experiment indicate that customer satisfaction with a product is influenced by the effort expended to acquire the product, and the expectations concerning the product. Specifically, the experiment suggests that satisfaction with the product may be higher when customers expend considerable effort to obtain the product than when they use only modest effort. This finding is opposed to usual notions of marketing efficiency and customer convenience. The research also suggests that customer satisfaction is lower when the product does not come up to expectations than when the product meets expectations.